Engineering students' perceptions of graduate attributes : perspectives from two educational paths - Lee, Chien-Ching (2020)
This study aimed to provide insights on the perceptions of engineering students from two educational paths in Singapore of desired graduate attributes by employers. Research questions: (1) Do graduates from the polytechnic and junior college paths have similar perceptions with regard to the ranking of desirable graduate attributes? (2) If not, in what ways are their perceptions different? Literature review: A review of literature on employers’ ranking of desirable graduate attributes revealed mismatches in employers’ and graduates’ rankings. There has not been any published study on student awareness of employability skills in Singapore in particular. Hence, this study investigated the perceptions of final-year engineering students from two different educational paths of their ranking of graduate attributes. Methodology: The students were asked to rank eight attributes and explain their ranking from an employer’s perspective. Results: The findings show that communication, teamwork, and problem-solving were ranked the top three desirable attributes by both groups of students. However, polytechnic students seem to reflect greater familiarity and confidence in tackling workplace requirements compared to junior college students. The implications of the findings are presented.